2022
DOI: 10.3390/en15217945
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic and Exergoenvironmental Analysis of a Novel Power and Cooling Cogeneration System Based on Organic Rankine Cycle and Ejector Refrigeration Cycle

Abstract: A novel combined power and refrigeration system is proposed based on organic Rankine and jet refrigeration cycles. The system has a wider application range and can be adjusted to different cooling and evaporation temperatures. To meet the needs of diverse populations, the cooling and evaporation temperature can be as low as −60 degrees Celsius. The genetic algorithm is used to optimize the system, and the proposed system’s energy, exergy, economy, and environment are analyzed under optimal conditions. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Thermal efficiency, exergy efficiency, total investment cost, total exergy destruction rate, net power production capacity, and cycle cooling capacity at optimal conditions were 23.04%, 26.55%, 45,944.5 $/yr, 226 kW, 75.17 kW, and 111.6 kW, respectively. Tao et al [52] analyzed and optimized a combined power and refrigeration system based on ORC and ERC. The evaporation temperature was as low as −60 • C. The system was compared with others reported in the literature, finding that under the same operating conditions, the system's net power was increased by 12.52 kW, the thermal efficiency was increased by 4.27%, and the energy efficiency was increased by 2.57%.…”
Section: Integrated Cooling and Power Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal efficiency, exergy efficiency, total investment cost, total exergy destruction rate, net power production capacity, and cycle cooling capacity at optimal conditions were 23.04%, 26.55%, 45,944.5 $/yr, 226 kW, 75.17 kW, and 111.6 kW, respectively. Tao et al [52] analyzed and optimized a combined power and refrigeration system based on ORC and ERC. The evaporation temperature was as low as −60 • C. The system was compared with others reported in the literature, finding that under the same operating conditions, the system's net power was increased by 12.52 kW, the thermal efficiency was increased by 4.27%, and the energy efficiency was increased by 2.57%.…”
Section: Integrated Cooling and Power Systemsmentioning
confidence: 99%
“…Also, many studies have been reported for the simultaneous production of power and cooling, but most of these studies integrate a VCRC into an ORC [47,49,50]. Also, many systems have used an ERC for cooling purposes [51][52][53]. Only a few studies have integrated an ACS for cooling production [54][55][56][57], and in fact, just the system analyzed by Grosu et al [59] was driven by solar energy.…”
Section: Integrated Cooling and Power Systemsmentioning
confidence: 99%
“…The main advantage of genetic algorithms is the ability to solve complex systems with many elements [161]. This algorithm can be used for optimization [162,163]. It has a simple structure consisting of seven steps [164].…”
mentioning
confidence: 99%